Climate change and public health - Levy, Barry S.; Patz, Jonathan (Oxford University Press, 2015)
Orchestrating and coordinating contributions from more than 75 selected public health specialists and environmental scientists, the editors have developed a concise and comprehensive book that represents a core curriculum on climate change and public health, including key strategies for adaptation and mitigation.